Temporal variation in community structure of Dragnet (Pukat Tarik) fishery in relation to ecological variables in an inshore area of Sarawak, Malaysia - M. K., Abu Hena; U., Kumar; M. H., Idris; N. U., Karim; Ismail, J.; Jaafar, N. M. S. N. (Prince of Songkla University, 2021)
Inshore waters are crucial for fisheries since such areas show a wide range of variations in ecology, mostly consideredto shape biotic ecosystems. Despite major fishing activities off Bintulu coast located along the South China Sea operating in theinshore areas and significantly contributing to local fisheriesโ economy by Pukat Tarik (dragnet), temporal exchange of fisheriescomposition in terms of ecological parameters has been little studied. Therefore, temporal changes in pull net fisheriescomposition and assemblages in relation to the ecological parameters in the inshore waters of Bintulu coast, Sarawak, wereobserved from May 2016 to April 2017. A total of 63 species belonging to 15 orders of 40 families were recorded, and 11 speciesfound ubiquitous. Species diversity (Hยด) was recorded higher (2.61) in northeast monsoon, and lower (0.51) in inter-monsoonseason, yet the species richness and diversity did not show temporal differences (p>0.05). Among the species Kurtus indicus wasrecorded the most abundant (58% of the total catch) followed by Photopectoralis bindus (15%) and Opisthopterus tardoore(7%); and the species abundance showed significant temporal differences (p<0.05). However, temperature, salinity, pH,dissolved oxygen (DO) and rainfall showed classical temporal differences (p<0.05), and no significant difference was found inchlorophyll a and water nutrients. ANOSIM indicated that the significant difference of assemblages among season was moreapparent than within season (Global R=0.65, p<0.001). The canonical correspondence analysis indicated total suspended solids,dissolved oxygen (DO), transparency, rainfall and salinity as the most important ecological factors affecting fish assemblagestructure. The inshore fisheries of Bintulu coast were found immensely rich and profoundly related to ecological factors, whichwill eventually help manage this fishery resource in the future in tropical coastal waters of the South China Sea.